INVESTIGATION OF INFRARED DRYING OF POMEGRANATE BY-PRODUCTS - Doymaz, I.; Kipcak, A. S. (YILDIZ TECHNICAL UNIV, 2018)
In the present study, infrared radiation drying, representative of the innovative drying method, was chosen to perform comparative study at different infrared power levels. Infrared drying of pomegranate by-products was dried at 88, 104, 125, 146 and 167 W power levels. The results showed that the infrared power has a significant effect on the drying characteristics of pomegranate by-products. Drying time was reduced from 270 to 60 min as the infrared power level increased from 88 to 167 W. The falling-rate period proved to be the main stage of infrared drying. Three thin-layer drying models (Aghbashlo et al., Jena & Das and Midilli & Kucuk) were fitted to the experimental data. The drying data (moisture ratio versus drying time) were successfully fitted to Aghbashlo et al. model. Fick's law of diffusion was used to determine the effective moisture diffusivity, which varied between 3.296 x 10(-9) to 1.431 x 10(-8) m(2)/s. Activation energy was estimated by a modified Arrhenius type equation as 4.424 kW/kg.
Keywords: Infrared Drying; Pomegranate By-Product; Modelling; Effective Moisture Diffusivity; Activation Energy; QUALITY; KINETICS; SLICES; BED; Thermodynamics